Myeloid lineage skewing due to exacerbated NF-κB signaling facilitates osteopenia in Scurfy mice - Chen, T H-P (Cell Death Dis, 2015)
Immune surveillance through Foxp3+ regulatory T cells plays a crucial role in bone homeostasis. Scurfy, the mouse model of autoimmune IPEX syndrome, bears a loss-of-function mutation in Foxp3 that leads to multi-organ inflammation. Herein, we report that scurfy mice exhibit severe bone loss mediated by accelerated osteoclastogenesis. Mechanistically, Foxp3 deficiency results in the upregulation of NF-κB in T helper cells through the loss of repressive Foxp3/NEMO interaction, thereby unleashing NF-κB-mediated over-production of pro-osteoclastogenic cytokines. Flow cytometry analysis shows marked increase in lin(-)Sca-1(+)c-kit(+) hematopoietic stem cells (LSK HSCs) and granulocyte/macrophage progenitors (GMPs) in bone marrow of scurfy mice with corresponding exacerbated osteoclastogenic potential, implying that osteoclast progenitors are affected at a very primitive stage in this disorder. Scurfy LSK HSCs exhibit greater sensitivity to M-CSF and contain abundant PU.1+ Sf LSK HSCs compared with WT. Accordingly, genetic or pharmacological inhibition of M-CSF or mTOR signaling, but not IL-17 signaling, attenuates osteoclastogenesis and osteopenia in scurfy. Thus, our study suggests that Foxp3 deficiency leads to osteopenia owing to dysregulated NF-κB activity and subsequent cytokine-mediated hyper-proliferation of myeloid precursors, and positions the NF-κB pathway as a potential target for therapeutic intervention for this disorder.